Association of Prenatal Ambient Air Pollution Exposure With Placental Mitochondrial DNA Copy Number, Telomere Length and Preeclampsia - Mandakh, Yumjirmaa; Oudin, Anna; Erlandsson, Lena; Isaxon, Christina; Hansson, Stefan R.; Broberg, Karin; Malmqvist, Ebba (Frontiers in Toxicology, 2021)
Background: Studies have shown that ambient air pollution is linked to preeclampsia (PE), possibly via generation of oxidative stress in the placenta. Telomere length and mitochondrial DNA copy number (mtDNAcn) are sensitive to oxidative stress damage. Objective: To study the association between prenatal exposure to ambient nitrogen oxides (NOx, a marker for traffic-related air pollution), and PE, as well as potential mediation effects by placental telomere length and mtDNAcn. Methods: This is a cross-sectional study of 42 preeclamptic and 95 arbitrarily selected normotensive pregnant women with gestational ambient NOx exposure assessment in southern Scania, Sweden. Hourly concentrations of NOx were estimated at the residential addresses by a Gaussian-plume dispersion model with 100 × 100 m spatial resolutions and aggregated into trimester-specific mean concentrations. Placental relative mtDNAcn and telomere length were measured using qPCR. Linear and logistic regression models were used to investigate associations, adjusted for perinatal and seasonal characteristics. Results: Exposure was categorized into low and high exposures by median cut-offs during first (11.9 μg/m3; interquartile range (IQR) 7.9, 17.9), second (11.6 μg/m3; IQR: 7.1, 21.1), third trimesters (11.9 μg/m3; IQR: 7.7, 19.5) and entire pregnancy (12.0 μg/m3; IQR: 7.6, 20.1). Increased risk of PE was found for high prenatal NOx exposure during the first trimester (OR 4.0; 95% CI: 1.4, 11.1; p=0.008), and entire pregnancy (OR 3.7; 95% CI: 1.3, 10.4; p=0.012). High exposed group during the first trimester had lower placental relative mtDNAcn compared with low exposed group (-0.20; 95% CI: -0.36, -0.04; p=0.01). Changes in relative mtDNAcn did not mediate the association between prenatal NOx exposure and PE. No statistically significant association was found between placental relative telomere length, prenatal NOx exposure and PE. Conclusion: In this region with relatively low levels of air pollution, ambient NOx exposure during the first trimester was associated with reduced placental relative mtDNAcn and an increased risk of PE. However, we did not find any evidence that mtDNAcn or TL mediated the association between air pollution and PE. Future research should further investigate the role of mtDNAcn for pregnancy complications in relation to exposure to ambient air pollution during pregnancy.